Studying the effect of ore texture on the Bond Work Index at the Mahd Ad Dahab Gold Mine: a case study (Rudarsko-geološko-naftni zbornik, 2020)
The grinding process in industrial ball mills is the basic unit and most energy-consuming component. Therefore, great economic gains will be achieved if a slight improvement occurs in the efficiency of grinding. The variation of gold ore petrography affects its mechanical properties which in turn, affects the grinding process. In this investigation, different gold-bearing ore types from the Mahd Ad Dahab gold mine were tested. As a part of the current study, some of the me- chanical and physical properties including strength properties, geological characterization and Bond work index were determined. This investigation showed that the Bond work index increases with an increase in rock strength properties. The maximum difference in the Bond work index for the five tested gold ores was 11%. Whereas, an average interval between the two-sequence types of the tested ore was approximately 2.5%.